Optimizing The Performance of Civil Servants: A Case Study at The Tax Counseling and Consulting Service Office (KP2KP) - Hardiyansyah Hardiyansyah; Aspi Zaitun; Ade Firmansyah; Nidyawati Nidyawati (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2020)
The performance of civil servants in the taxation sector will determine the success of state tax revenue. The purpose of this study was to determine and analyze the performance optimization of the KP2KP employees. Qualitative research with an explanatory research approach. Primary data sources were carried out through in-depth interviews with informants from the KP2KP, field observations and collection of written documentation. After analyzing the data, the researcher found that the optimization of the performance of civil servants with limited human resources can be realized through empowerment, development, competency improvement, employee motivation through adequate compensation and leadership effectiveness in KP2KP. Research results are very important for policy makers in perfecting their policies. Optimizing the performance of civil servants through empowerment, development, increasing competence, providing employee motivation through adequate compensation and leadership effectiveness in KP2KP. This study presents different points of view on the topic of civil servant performance. Increasing the performance optimization of civil servants with limited human resources is a new thing and according to the author's knowledge, the results of this study are the first to explain the increase in the performance optimization of KP2KP employees in Ogan Ilir Regency. Abstrak Kinerja PNS di bidang perpajakan sangat menentukan keberhasilan penerimaan pajak negara. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis optimalisasi kinerja pegawai KP2KP. Penelitian kualitatif dengan pendekatan penelitian eksplanatori. Sumber data primer dilakukan melalui wawancara mendalam dengan informan dari KP2KP, observasi lapangan dan pengumpulan dokumentasi tertulis. Setelah menganalisis data, peneliti menemukan bahwa optimalisasi kinerja PNS dengan sumber daya manusia yang terbatas dapat diwujudkan melalui pemberdayaan, pengembangan, peningkatan kompetensi, motivasi pegawai melalui kompensasi yang memadai dan efektivitas kepemimpinan di KP2KP. Hasil penelitian sangat penting bagi pengambil kebijakan dalam menyempurnakan kebijakannya. Mengoptimalkan kinerja PNS melalui pemberdayaan, pengembangan, peningkatan kompetensi, pemberian motivasi pegawai melalui kompensasi yang memadai dan efektivitas kepemimpinan di KP2KP. Studi ini menyajikan sudut pandang yang berbeda tentang topik kinerja pegawai negeri. Peningkatan optimalisasi kinerja PNS dengan sumber daya manusia yang terbatas merupakan hal baru dan menurut pengetahuan penulis, hasil penelitian ini merupakan yang pertama menjelaskan peningkatan optimalisasi kinerja pegawai KP2KP di Kabupaten Ogan Ilir. Kata Kunci : Kinerja Pegawai, Pelayanan, Penyuluhan, Perpajakan